2002
DOI: 10.1104/pp.006833
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Nodule-Specific Transcripts in the Model Legume Medicago truncatula  

Abstract: The Medicago truncatula expressed sequence tag (EST) database (Gene Index) contains over 140,000 sequences from 30 cDNA libraries. This resource offers the possibility of identifying previously uncharacterized genes and assessing the frequency and tissue specificity of their expression in silico. Because M. truncatula forms symbiotic root nodules, unlike Arabidopsis, this is a particularly important approach in investigating genes specific to nodule development and function in legumes. Our analyses have reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
172
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(181 citation statements)
references
References 97 publications
6
172
0
3
Order By: Relevance
“…These results suggested that at least some of the genes involved in nodulation are evolved from broadly conserved pathways of plant development (Parniske and Downie, 2003;Szczyglowski and Amyot, 2003). This view was further supported by Fedorova et al (2002), who identified 340 tentative consensus sequences with nodule-specific expression patterns, approximately 40% of which shared sequence homology to sequences from non-legumes. It will be a challenging task to undertake the discovery and dissection of the function of the genes that are required for nodulation but are conserved across plant families (e.g.…”
Section: Legume-arabidopsis Comparison: Implication Of Correlated DIVmentioning
confidence: 72%
See 1 more Smart Citation
“…These results suggested that at least some of the genes involved in nodulation are evolved from broadly conserved pathways of plant development (Parniske and Downie, 2003;Szczyglowski and Amyot, 2003). This view was further supported by Fedorova et al (2002), who identified 340 tentative consensus sequences with nodule-specific expression patterns, approximately 40% of which shared sequence homology to sequences from non-legumes. It will be a challenging task to undertake the discovery and dissection of the function of the genes that are required for nodulation but are conserved across plant families (e.g.…”
Section: Legume-arabidopsis Comparison: Implication Of Correlated DIVmentioning
confidence: 72%
“…Motif analysis identified three major gene families from this putative legume-specific gene set, including F-box-related proteins, Pro-rich proteins, and Cys cluster proteins. In particular, the more than 300 Cys cluster proteins, with predicted similarity to defensins, represent approximately 1% of expressed genes in Medicago, primarily from nodules (Fedorova et al, 2002;Mergaert et al, 2003;Graham et al, 2004). Work is under way to characterize these putative legumespecific genes using both forward and reverse genetic tools (K. VandenBosch, personal communication).…”
Section: Legume-arabidopsis Comparison: Implication Of Correlated DIVmentioning
confidence: 99%
“…Of the total collection of tags, only 56% were represented in the MTGI by ESTs. Strikingly, for the tags linked to an ESTcluster (tentative consensus sequences), only 23% of them had a corresponding EST in the senescent nodule library (Fedorova et al, 2002), indicating that this library is only a limited representation of the nodule senescence transcriptome. The gene tags were grouped into 19 functional classes derived from the Medicago EST Navigation System (Journet et al, 2002;Fig.…”
Section: Gene Tag Sequence Analysismentioning
confidence: 99%
“…We sorted TCs to identify predicted genes with particular expression patterns, based on the libraries of origin of the ESTs in the TCs. For example, Fedorova et al (2002) identified nodulespecific expressed genes, including some unique classes of genes. We have recently released MtDB, a new database that clusters all public M. truncatula ESTs into about 17,000 contigs plus a similar number of singletons (Lamblin et al, 2003; http://www.…”
Section: Analysis Of Medicago Gene Function During Interactions Withmentioning
confidence: 99%
“…Some of these sequences appear to be members of gene families, based on clustering analyses. One spectacular example is a group of more than 300 putatively secreted proteins that are Cys rich and were previously identified as nodule specific (Fedorova et al, 2002). Despite the lack of apparent sequence similarity of leguminosins to known sequences from other organisms, motif searching has provided clues to the functions for some members of this group.…”
Section: Sifting For Novel Expressed Sequences Among Legume Estsmentioning
confidence: 99%